Protective Efficacy of Decreasing Antigen Doses of a Chlamydia abortus Subcellular Vaccine Against Ovine Enzootic Abortion in a Pregnant Sheep Challenge Model - Morag Livingstone; Kevin Aitchison; Javier Palarea-Albaladejo; Francesco Ciampi; Clare Underwood; Antonia Paladino; Francesca Chianini; Gary Entrican; Sean Ranjan Wattegedera; David Longbottom (Vaccines)
Background/Objective: Chlamydia abortus, the cause of ovine enzootic abortion, is a zoonotic bacterial pathogen and one of the most infectious causes of foetal death in sheep worldwide. Although the disease can be controlled using commercial inactivated and live whole-organism vaccines, there are issues with both, particularly concerning efficacy and safety. Recently, we have described the development of a new COMC (chlamydial outer membrane complex) vaccine based on a detergent-extracted outer membrane protein preparation of the pathogen, which can be delivered in a single inoculation and is both efficacious and safe. Methods: In this study, we have evaluated the COMC vaccine further in a dose–response titration of the chlamydial antigen content of the vaccine (from 20 to 2.5 µg in seven experimental groups) using an established pregnant sheep challenge model. Results: No obvious dose–response relationship was observed across the groups, with a single abortion event occurring in four of the groups and three in the lowest dose group (2.5 µg). No abortions occurred in the 15 and 10 µg groups. The abortion rates (0–14%) were significantly below that of the challenge control group (33%). A similar reduction in bacterial shedding of infectious organisms following parturition was observed in the vaccinated groups compared to the challenge control group, which is important in terms of reducing potential transmission to naive animals. Conclusions: The results show that a dose of 10 µg antigen in the vaccine will be optimal in terms of maximising efficacy, reducing shedding at parturition, and ensuring it is cost-effective to produce for commercial manufacture.